2022
DOI: 10.1155/2022/9242243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Body Composition in Men with Hormone-Sensitive Metastatic Prostate Cancer: A Pilot Study Examining Differences by Race

Abstract: Black men treated with frontline therapies for metastatic prostate cancer (MPC) show better clinical outcomes than non-Black men receiving similar treatments. Variations in body composition may contribute to these findings. However, preliminary data are required to support this concept. We conducted a retrospective cohort study for all men with MPC evaluated at our center over a 4-year period, collecting demographic and clinical data (N = 74). Of these, 55 men had diagnostic computed tomography images to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The description of included studies is presented in Table 1 . Observational studies were conducted in ethnically diverse groups of PCa patients, where the sarcopenia was assessed either twice (at the baseline and in the follow up) [ 22 , 23 , 25 , 26 , 27 ] or only once during the ADT treatment [ 28 , 29 ]. The largest group of PCa patients was found in Chiang et al [ 25 ] and therefore this study will have the greatest impact on the meta-analysis performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The description of included studies is presented in Table 1 . Observational studies were conducted in ethnically diverse groups of PCa patients, where the sarcopenia was assessed either twice (at the baseline and in the follow up) [ 22 , 23 , 25 , 26 , 27 ] or only once during the ADT treatment [ 28 , 29 ]. The largest group of PCa patients was found in Chiang et al [ 25 ] and therefore this study will have the greatest impact on the meta-analysis performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the sarcopenia assessment methodology and time to follow up used in single studies were differentiated, which could influence the obtained results. Nevertheless, no association with progression-free survival or overall survival was indicted [ 22 , 23 , 25 ]) ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-seven [ 20 , 22 , 25 , 27 , 30 , 31 , 33 36 , 38 , 41 , 48 , 49 , 51 58 , 60 , 62 , 70 , 71 , 78 ] of the 54 studies reported results on overall survival (OS) or all-cause mortality, 11 studies [ 21 24 , 26 , 31 , 37 , 38 , 44 , 50 , 61 ] reported results on prostate cancer specific mortality (PCSM), and 11 studies [ 29 , 32 , 39 , 46 , 62 65 , 73 , 77 , 80 ] reported results on OS or PCSM in patients on specific mPC treatments, with some of the studies reporting on more than one survival outcome. Nine studies [ 3 , 28 , 40 , 42 , 43 , 45 , 47 , 59 , 79 ] reported only descriptive data, described racial groups other than Black, White, Hispanic, Asian, or Native American, such as Maori, Thai, Malaysian, or conducted separate analyses within each racial group. An overview of these studies is included in Table A.…”
Section: Resultsmentioning
confidence: 99%
“…reporting on more than one survival outcome. Nine studies [3,28,40,42,43,45,47,59,79] reported only descriptive data, described racial groups other than Black, White, Hispanic, Asian, or Native American, such as Maori, Thai, Malaysian, or conducted separate analyses within each racial group. An overview of these studies is included in Table A.5.…”
Section: Study Characteristicsmentioning
confidence: 99%